METODE KRITIK MATAN HADIS PRESPEKTIF MASRUKHIN MUKHSIN - Hilda Husaini Rusdi (Al-Shamela : Journal of Quranic and Hadith Studies, 2023)
This paper departs from the author's hypothesis regarding to the critical studies of matan used by academics in measuring the validity of hadith. The critical theory used by these academics still needs to be studied and re-criticized whether it is specific to the theory developed by the Muhaddisin Mutaqaddimin and Mutaakhirin scholars who are known for their accuracy. Masrukhin Mukhsin reflects on the views of the hadith scholars above and schematizes the theory of Muqoronah, Muaradlah, al-Taufiq, I'lat, Syadz, contemporary as an answer to the anxiety of academics in studying the accuracy of matan. Departing from this, this paper will discuss 1) What are the methods used by researchers in criticizing the hadith matan? 2) Is the method they use enough to prove the validity of a hadith matan? This paper is a library research study with an analytical-descriptive approach. The results of this paper are proving that the critique method used by academics still does not use the right method in studying the critique of hadith matan, so it still needs to be re-examined regarding to the validity of the hadith matan.